High-precision fiber-optic temperature sensor based on Fabry-Perot interferometer with reflective thin-film multilayer structures - Moor, Ia.D.; Konnov, K.A.; Plotnikov, M.Yu; Volkov, A.V.; Varzhel, S.V.; Konnov, D.A.; Strigalev, V.E. (Nauchno-tekhnicheskiĭ vestnik informat͡s︡ionnykh tekhnologiĭ, mekhaniki i optiki, 2024)
An embodiment of a fiber-optic temperature sensor based on a Fabry-Perot interferometer and a scheme for interrogating an experimental sample of the sensor are proposed. The proposed solution makes it possible not to use expensive spectral measuring devices (spectrum analyzer, interrogator). The region of free dispersion and the phase sensitivity of the developed Fabry-Perot interferometer were determined in the temperature range from 20 °C to 590 °C. The accuracy of measuring the ambient temperature is calculated. The long-term stability of the measuring setup at room temperature has been evaluated. The phase shift of the Fabry-Perot interferometer with temperature change was registered. The design of the Fabry-Perot interferometer is implemented using reflective thin-film multilayer structures obtained by stage-bystage electron-beam deposition in vacuum on polished end cleavages of an optical fiber. The interferometer interrogation method is based on the use of a vertical-cavity surface-emitting laser (VCSEL) operating in a pulsed mode. The principle of registering the phase shift of the interferometer with a change in temperature is based on the use of auxiliary modulation of laser radiation along the wavelength due to modulation (periodic change) of the duration of optical pulses. Auxiliary modulation makes it possible to obtain additional harmonic components in the interferometer signal, which are further used in homodyne demodulation to restore the interferometer phase shift signal proportional to the change in the optical path difference between the interferometer mirrors. The design of the high-temperature sensor is based on a Fabry-Perot interferometer the reflecting mirrors of which are five alternating layers of thin films of TiO2 and Al2O3. Based on the results of the temperature experiment, it was concluded that an increase in the ambient temperature leads to a decrease in the free dispersion region of the Fabry-Perot interferometer. The conclusion made is consistent with the theoretical data. According to the results of the experiment, it is shown that the phase sensitivity of the interferometer to temperature changes is 0.94 rad/K. The accuracy of temperature measurements at the 3σ level was 0.017 K. The results of the study may be of great importance in creating systems for monitoring temperatures above 300 °C. The use of such an interferometer makes it possible to carry out high-precision relative temperature measurements.